Power Management System (PMS) Sebagai Kontrol Utama Dalam Perkembangan Power Listrik Kapal - Eka Darmana; Fajar Pujiyanto (Majalah Ilmiah Bahari Jogja, 2021)
Shipboard electrical power was introduced in the 19th century, electricity as a source of energy for operating vessel is used for lighting, communication, navigation, monitoring, alarm systems, running electric motors, and high voltage installations as the main propulsion. The first electrical installation by commercial ship SS Columbia with a DC electical power, followed by an AC induction motor with a diesel engine. The new technology of electrical power is All Electric Ship (AES) by the passenger ferry Ampere, is the first ship in the world to use fully battery driven and operate regularly in Norway waters. Currently the world engineers are developing new ship designs with a hybrid power, which combines two or more integrated power sources to get high-efficiency power. In this paper uses a qualitative description method with reference to literature studies. The development of electricity from each generation regarding electric power sources, automatic control and power management is the material to be discussed in this paper. The Power Management System (PMS) is a functionally integrated control system to optimize power allocation and energy distribution. PMS keeps electrical power working without any fault, disruptions or system failures while the ship is operating. PMS controls power in a safe and balanced manner between power generation and distribution of ship electrical power.